The Role of Mass Media in Strengthening the Modern Legal State - Anwar, Heril; Kusdarini, Eny (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
This article discusses the role of the mass media in strengthening the modern rule of law. This type of research is library research carried out using literature from previous studies. This systematic literature review method is a research method that identifies, assesses, and interprets all findings on a research topic, to answer predetermined research questions. The mass media can help maintain press freedom, increase government transparency and accountability, and provide information and public oversight that can help ensure that laws are enforced fairly and democratically. In addition, the mass media can also encourage public participation in the legal process, provide a forum for discussion and debate on controversial legal issues, and give voice to the community in terms of voicing their aspirations and interests. However, the mass media also need to pay attention to the challenges in their role, such as ensuring that they not only strengthen the interests of existing governments or economic forces, but also help safeguard the interests of society and justice